2022
DOI: 10.3389/fendo.2022.959276
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome activation as a link between obesity and thyroid disorders: Implications for an integrated clinical management

Abstract: Obesity is strongly associated with chronic low-grade inflammation. Obese patients have an increased risk to develop thyroid autoimmunity and to became hypothyroid, suggesting a pathogenetic link between obesity, inflammation and autoimmunity. Moreover, type 2 diabetes and dyslipidemia, also characterized by low-grade inflammation, were recently associated with more aggressive forms of Graves’ ophthalmopathy. The association between obesity and autoimmune thyroid disorders may also go in the opposite direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 143 publications
0
15
0
Order By: Relevance
“…Systemic inflammation induced by obesity combined with insulin resistance are responsible for increased production of reactive oxygen radical species (ROS) that activate the inflammasome complex in different tissues. [43][44][45] D'Ippolito et al observed that the endometrium of women with a history of RM has a higher expression of inflammasome NALP-3 and ASC protein, an increased activation of caspase-1, and increased levels of IL-1β and IL-18 compared to control. 46 Obesity and an unhealthy diet can induce changes in the gut microbiome with an impact on the innate immune system, such as an increase in the Th1/Th17 response and a reduction in Treg lymphocytes.…”
Section: Immune System and Rmmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammation induced by obesity combined with insulin resistance are responsible for increased production of reactive oxygen radical species (ROS) that activate the inflammasome complex in different tissues. [43][44][45] D'Ippolito et al observed that the endometrium of women with a history of RM has a higher expression of inflammasome NALP-3 and ASC protein, an increased activation of caspase-1, and increased levels of IL-1β and IL-18 compared to control. 46 Obesity and an unhealthy diet can induce changes in the gut microbiome with an impact on the innate immune system, such as an increase in the Th1/Th17 response and a reduction in Treg lymphocytes.…”
Section: Immune System and Rmmentioning
confidence: 99%
“…Obesity is recognized as a chronic low‐grade inflammatory disease, being responsible for triggering an imbalance of the immune response in the adipose tissue and systemically. Systemic inflammation induced by obesity combined with insulin resistance are responsible for increased production of reactive oxygen radical species (ROS) that activate the inflammasome complex in different tissues 43–45 . D'Ippolito et al.…”
Section: Immune System and Rmmentioning
confidence: 99%
“…The concept of orbital inflammation connects delicate mechanisms of the disease spectrum where at one end lies the autoimmune reaction typically associated with GD or HT and at the other newer concept of inflammasome activation along with a cohort of metabolic factors. 32,33 The pathogenesis of TED involves hereditary factors, environmental factors, thyroid-stimulating hormone receptor (TSHR) antibodies, and type 1 insulin-like growth factor receptors (IGF-1R). 32 Smoking is a common underlying environmental factor in TED pathogenesis.…”
Section: Ted With T2dmmentioning
confidence: 99%
“…Thyroxine hormone also increases catecholamines that stimulate hepatic gluconeogenesis, with active lipolysis and increased levels of free fatty acids. 33 The marked hepatic glucose release is responsible for IR, hyperinsulinemia, and low glucose tolerance. 42 IR causes hyperinsulinemia, which causes decreased availability of IGF binding proteins, increasing the bioavailability of IGF1.…”
Section: Ted With T2dmmentioning
confidence: 99%
See 1 more Smart Citation